A 5-Year Follow-Up of The Benefits of an Exercise Training Program in Liver Recipients Transplanted Due to Familial Amyloidotic Polyneuropathy. (December 2018) - Tomás, Maria Teresa; Melo, Xavier; Mateus, Élia; Gonçalves, Mafalda; Barroso, Eduardo; Santa-Clara, Helena
Background: Supervised (SE) and home-based exercise (HBE) training regimes are effective on reconditioning patients with familial amyloidotic polyneuropathy (FAP) after liver transplantation, but research of the long-term retention of the benefits attained in patients with FAP has not yet been conducted. Purpose: In this 5-year follow-up study, we aimed to determine whether the exercise training gains in body composition, physical activity, and function promoted by a 24-week SE or HBE training regimes are retained in patients with FAP who resume normal activity. Methodology: Sixteen liver-transplanted patients with FAP were reassessed for body composition (dual X-ray absorptiometry), physical activity (questionnaire), and function (handgrip strength and 6-minute walk test). Results: Total body fat increased with both exercise regimes during follow-up ( P < .05; η 2 = 0.432-0.625) as well as femoral neck bone density ( P = .048; η 2 = 0.119). However, gains in upper limbs muscle quality during follow-up ( P < .001; η 2 = 0.597) were only found in the SE group ( P = .042; η 2 = 0.245). Both exercise regimes showed retaining aptitudes in walking capacity ( P < .05; η 2 = 0.329-0.460) and muscle mass ( P = .05; η 2 = 0.245). Still, none could retain the physical activity levels. Conclusion: Long-term resumption of normal activity following a 24-week SE or HBE regime in patients with FAP resulted in loss of exercise induced increases in physical activity but counterweighted postoperative losses in bone mineral density and substantially retained the benefits in walking capacity, muscle mass, and quality, in particular, in the SE group.